THE ISSUE OF TRADITIONAL MEDICINE AND WOMEN DOCTORS IN TURKESTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with the creation of medical institutions in Turkestan and the organization of womens medicine.